INVESTIGATING THE RELATIONSHIP BETWEEN CORPORATE CITIZENSHIP CULTURE AND ORGANISATIONAL PERFORMANCE IN THE MALAYSIAN CONTEXT - Wan Kalthom Yahya; Norbani Che Ha (Asian Academy of Management Journal, 2014)
Contemporary organisations are required to be responsible to their shareholders, customers, employees, communities and ecology in all aspects of their operations in order to gain a competitive advantage. An organisation's obligations toward society, known as corporate citizenship, are economic, legal, ethical, and discretionary. Corporate citizenship reflects one view of social responsibility that relates to the social responsibilities of organisations toward their stakeholders. Thus, this study examines the relationship between corporate citizenship culture and organisational performance. Overall, 261 respondents from a total population of 1379 were used in analysing the data. The units of analysis of this study are publicly listed companies in Malaysia. The findings suggest that all elements of corporate citizenship culture are significantly related to organisational performance, especially ethical citizenship. The results support theoretical predictions and reveal interesting findings that can help organisations to better understand how their performance affects society's perceptions of them and help change organisational behaviour to meet public expectations.